William Blake on his poetry and painting a study of A descriptive catalogue, other prose writings, and Jerusalem - Adams, Hazard, 1926- (McFarland & Co., Publishers, 2011)
"Blake was not merely a poet, but a prolific commentator on both his own art and art in general. This is the first text to collect and discuss all of the writings in one volume. Topics include his opinions on his predecessors and his contemporaries, his reaction to critics, and his artistic intentions"--Provided by publisher.